2010
DOI: 10.14227/dt170410p41
|View full text |Cite
|
Sign up to set email alerts
|

AAPS Workshop on the Role of Dissolution in QbD and Drug Product Life Cycle: A Commentary

Abstract: This is a summary report of the "AAPS Workshop on the Role of Dissolution in QbD and Drug Product Life Cycle" organized by the AAPS In Vitro Release and Dissolution Testing (IVDRT) Focus Group. Representatives from the pharmaceutical industry, regulatory authorities, and academia in the U.S. and Europe attended this workshop to discuss the role of dissolution in a Quality by Design (QbD) setting and its relevance in drug product development. Other areas of discussion included IVIVC/R and hot topics like alcoho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 3 publications
(1 reference statement)
0
3
0
Order By: Relevance
“…The experimental data for glyburide had shown that low quality FaSSIF was the best media to establish an in vivo/in vitro correlation (IVIVC) and was, therefore, used in this study only (15,16). In a quality by design (QbD) approach, dissolution should reflect ideally the in vivo product performance (17)(18)(19). Starting out with simulated in vitro dissolution data as an input to an in vivo prediction software such as GastroPlus™ may help to establish IVIVC in the later stages of the drug development process.…”
Section: Percent Of Particles Distributionmentioning
confidence: 99%
“…The experimental data for glyburide had shown that low quality FaSSIF was the best media to establish an in vivo/in vitro correlation (IVIVC) and was, therefore, used in this study only (15,16). In a quality by design (QbD) approach, dissolution should reflect ideally the in vivo product performance (17)(18)(19). Starting out with simulated in vitro dissolution data as an input to an in vivo prediction software such as GastroPlus™ may help to establish IVIVC in the later stages of the drug development process.…”
Section: Percent Of Particles Distributionmentioning
confidence: 99%
“…With the introduction of QbD by the Food and Drug Administration in 2004, pharmaceutical companies intensified their efforts to reach real-time release of industrial batches, thus reducing postprocessing quality control delays, the goal being to guarantee finished product quality and reduce product costs (International Conference on Harmonisation: Guidance on Q8, 2009). Obviously, the replacement of this test by a less resource-intensive technique through a QbD approach would be beneficial to the pharmaceutical industry (Tong and Lozano, 2009;D'Souza and Lozano, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that certain material attributes as well as manufacturing process parameters affect the results of dissolution tests performed on finished products. For example, several studies conclude that API dissolution and disintegration are linked: indeed the presence of disintegrants in tablets determines release rates and, consequently, physiological API availability (D'Souza and Lozano, 2010).…”
Section: Introductionmentioning
confidence: 99%